2023
DOI: 10.1038/s41598-023-44304-2
|View full text |Cite
|
Sign up to set email alerts
|

Formulation and evaluation of simvastatin cubosomal nanoparticles for assessing its wound healing effect

Lamiaa M. Ahmed,
Khaled M. A. Hassanein,
Fergany A. Mohamed
et al.

Abstract: Wound healing is one of the most challenging medical circumstances for patients. Pathogens can infect wounds, resulting in tissue damage, inflammation, and disruption of the healing process. Simvastatin was investigated recently, as a wound healing agent that may supersede the present therapies for wounds. Our goal in this paper is to focus on formulation of simvastatin cubosomes for topical delivery, as a potential approach to improve simvastatin skin permeation. By this technique its wound healing effect cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 52 publications
1
1
0
Order By: Relevance
“…They also showed moderate neovascularization and polymorphonuclear cell presence across the healing phases. Previous studies support our findings: Ahmed et al demonstrated re-epithelialization with SIM cubosomal nanoparticles [ 33 ]. Farghaly Aly et al showed complete epithelialization with SIM polymeric nanoparticle gel [ 34 ], as well as minimal inflammation and mature collagen fiber formation.…”
Section: Resultssupporting
confidence: 92%
“…They also showed moderate neovascularization and polymorphonuclear cell presence across the healing phases. Previous studies support our findings: Ahmed et al demonstrated re-epithelialization with SIM cubosomal nanoparticles [ 33 ]. Farghaly Aly et al showed complete epithelialization with SIM polymeric nanoparticle gel [ 34 ], as well as minimal inflammation and mature collagen fiber formation.…”
Section: Resultssupporting
confidence: 92%
“…By formulating simvastatin cubosomes for topical delivery, the study performed by Ahmed et al [ 130 ] introduced an innovative strategy to enhance simvastatin’s skin permeation, thereby optimizing the wound-healing effects of cubosomes. Cubosomes are distinct from solid nanoparticles and are liquid crystalline particles formed through self-assembly [ 131 ].…”
Section: Applications Of Statins In the Treatment Of Woundsmentioning
confidence: 99%